2022
DOI: 10.1177/17455057221133635
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and neurodevelopment in children and adolescents with Turner syndrome

Abstract: Objectives: Turner syndrome (TS) is a rare sex chromosome aneuploidy, with an incidence of four in 10,000 new-born girls. TS is often associated with impaired social communication skills, but the extent to which these are attributable to Autism Spectrum Disorders (ASD) is uncertain. We made standardized assessments of the mental health and associated neurodevelopmental disorders in children and adolescents with TS and report on the prevalence of concurrent conditions. Methods: Our sample comprised 127 girls wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…This suggests that reinforcement learning tasks may capture social cognitive challenges in Turner syndrome which are not readily assessed through self-reports. Interestingly, previous studies have suggested that self-ratings may underestimate social challenges in Turner syndrome 15 , 18 , 20 . As noted in the introduction, Turner syndrome is associated with executive function impairments 9 11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that reinforcement learning tasks may capture social cognitive challenges in Turner syndrome which are not readily assessed through self-reports. Interestingly, previous studies have suggested that self-ratings may underestimate social challenges in Turner syndrome 15 , 18 , 20 . As noted in the introduction, Turner syndrome is associated with executive function impairments 9 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Turner syndrome is associated with reduced social skills, an increased risk of having few friendship relations 12 15 , and difficulties with emotion recognition in faces 21 , 22 . The current study was the first to examine the effects of social feedback on reinforcement learning in Turner syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations